ESP8266-based Child Monitoring Bracelet Based on Smartphone Connected to Parents Smartphones - M Arif Rahman Hakim; Manik, Tomi Darmanto; Sheva Nurhaliza (Indonesian Journal of Electrical Engineering and Electronics, 2023)
Indonesia of the country with diverse tourism destinations. This invites many tourists who come to Indonesia. In addition to promising tourism, safety and comfort are also one of the selling points that tourists consider in choosing a vacation place. Many cases of child loss in Indonesia occur in tourism places that are crowded with visitors, therefore this study aims to design, build, and analyze ESP8266-based child monitoring bracelets connected to smart phones. It can send the current location of the wristband to the smartphone so that the position of the missing child can be tracked by the parents. The test is carried out by measuring the distance between the two tools, if the distance between the parent and the child's bracelet reaches a maximum distance (50 meters) then the alarm on each bracelet will sound and within a radius below the maximum distance when the parent activates the switch, the alarm on the child will be active and vice versa. It’s hoped that the existence of this smart bracelet can directly detect the location of children that are far from the reach of parents and can reduce cases of child loss that occur in tourism places crowded with visitors.